A prática do basquetebol por meninas nas aulas de educação física escolar no município de Volta Redonda: A visão dos professores - Severino, Claudio Delunardo; Miranda Gonçalves, Francisco José; Darido, Suraya Cristina [UNESP] (Desafio Singular, Lda, 2015)
This research aims to address girls participation in Physical Education classes, with a focus on Basketball as content. Teachers participated in the survey of public and private institutions in the city of Volta Redonda / RJ / Brazil in classes from 6th to 9th grade of elementary school. This was a quantitative and qualitative study of content analysis and as a data collection procedure, sixty teachers who opined on the issue investigated were interviewed. It was found that the reality of Physical Education in Volta Redonda has, in general, characteristics of a model based on the teaching of sports according to the conceptions subordinated high yield. It is also considered that Physical Education can be seen as an important ally in reaching goals linked to the formation of values, practicing Basketball in a school environment for girls may represent a new drawing and understanding of equal rights and not by hierarchy among learners.
The basketball practice for girls in school physical education in Volta Redonda: The the view of teachers
Keywords: Basketball; Girls; Physical education; School